Development of a Dust Monitoring System Using Internet of Things (IoT) Technology for Air Quality Control and Monitoring at Schools under the Jurisdiction of the Bangkok Secondary Educational Service Area. - Malaka, Kriangsak; Suksukon, Anusara; Khanthawongwattana, Kwanwichitrada; Paudel, Winai; Seemeephan, Kanokon; Junpen, Wanatsanan; Suksukont, Aekkarat (APHEIT Journal (SCIENCE and Technology), 2025)
This research aimed to design, develop a dust monitoring system utilizing the internet of things (IoT) to control and monitor air quality, specifically targeting particulate matter smaller than 10 microns (PM10) in schools under the Bangkok Metropolitan, and to evaluate users satisfaction towards the developed system. The design of the system integrates dust sensors with microcontrollers to transmit real-time data to a cloud-based platform and automatically activates a high-pressure mist spray system when dust levels exceed a predefined threshold through notifications delivered via a smartphone application. Research instruments included a user satisfaction questionnaire and an expert evaluation form. The findings revealed that the system effectively maintained dust levels within safe limits and achieved a high level of user satisfaction ( = 4.63, S.D. = 0.57). These results highlight the potential of IoT in promoting sustainable air quality management in schools and suggest its applicability as a prototype for smart school development and proactive environmental policy planning.